2009
DOI: 10.1124/mol.109.056291
|View full text |Cite
|
Sign up to set email alerts
|

Three Epigenetic Drugs Up-Regulate Homeobox GeneRhox5in Cancer Cells through Overlapping and Distinct Molecular Mechanisms

Abstract: Epigenetic therapy of cancer using inhibitors of DNA methyltransferases (DNMT) or/and histone deacetylases (HDACs) has shown promising results in preclinical models and is being investigated in clinical trials. Homeodomain proteins play important roles in normal development and carcinogenesis. In this study, we demonstrated for the first time that an epigenetic drug could up-regulate homeobox genes in the reproductive homeobox genes on chromosome X (Rhox) family, including murine Rhox5, Rhox6, and Rhox9 and hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 48 publications
4
46
1
Order By: Relevance
“…This is probably also the mechanism responsible for the dramatic induction of Rhox5 transcripts in 10T 1 ⁄ 2 mesenchymal stem cells reported earlier (Sasaki et al 1991). However, 5AzaC treatment also increased the levels of transcription-promoting histone modifications at the Pd, complicating the interpretation of its mechanism of action (Li et al 2009). In the future, it will be important to untangle the independent contributions of DNA methylation and histone modifications, a challenging task given that these two events are intimately linked at many levels (Berger 2007).…”
Section: The Pdmentioning
confidence: 96%
See 2 more Smart Citations
“…This is probably also the mechanism responsible for the dramatic induction of Rhox5 transcripts in 10T 1 ⁄ 2 mesenchymal stem cells reported earlier (Sasaki et al 1991). However, 5AzaC treatment also increased the levels of transcription-promoting histone modifications at the Pd, complicating the interpretation of its mechanism of action (Li et al 2009). In the future, it will be important to untangle the independent contributions of DNA methylation and histone modifications, a challenging task given that these two events are intimately linked at many levels (Berger 2007).…”
Section: The Pdmentioning
confidence: 96%
“…The selective expression pattern of Rhox genes in reproductive organs is conserved, as the rat Rhox genes are also selectively expressed in the ovary, testis, epididymis, and placenta , Maiti et al 1996a, MacLean et al 2005b, Morris et al 2006; JA MacLean, unpublished observations), and the two best-characterized human RHOX genes appear to be specifically expressed in the human testis (Geserick et al 2002, Wayne et al 2002a. While Rhox genes normally exhibit highly specific and regulated expression patterns, some Rhox family members are ubiquitously expressed in tumors, including mouse Rhox5, Rhox6, and Rhox9, as well as human RHOXF1 (Wilkinson et al 1990, Rao et al 2002a, Wayne et al 2002a, Li et al 2009). …”
Section: Expression and Functional Role Of Rhox Cluster Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, RHOXF2 expression was found in a variety of cancer tissues. Recently, several studies have reported that expression of RHOXF2 is regulated by some epigenetic mechanisms, especially in cancer tissues (16). These findings suggest that RHOXF2 plays a role in tumorigenesis and that it can be controlled epigenetically.…”
Section: Discussionmentioning
confidence: 83%
“…Homeobox proteins, share a DNA-binding homeodomain motif of 60 amino acids, and are transcription factors that regulate development. The Rhox genes belong to a recently discovered homeobox family whose members are clustered on the X chromosome (14)(15)(16) Rhox family consists of >30 members (14)(15)(16) (19). A murine pro-B cell line Ba/F3 was maintained in RPMI-1640 with 10% FCS and 1 ng/ml mouse IL-3 (mIL-3), and a murine myelomonocytic cell line HF6 was maintained in RPMI-1640 with 20% FCS and 10 ng/ml mIL-3 (11).…”
Section: Introductionmentioning
confidence: 99%